Selective immigration policies, migrants' education and welfare at origin - Simone Bertoli; Herbert Brücker (Institute for the Study of Labor (IZA), 2010)
Destination countries are progressively shifting towards selective immigration policies. These can effectively increase migrants' average education even if one allows for endogenous schooling decisions and education policies at origin. Still, more selective immigration policies reduce social welfare at origin.
Keywords: F22; J24; H52; O15; 330; international migration; selective immigration policies; education policies; social welfare